2011
DOI: 10.1126/scisignal.2002049
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Phosphorylation of the Gα-Interacting Protein GIV Promotes Activation of Phosphoinositide 3-Kinase During Cell Migration

Abstract: GIV (Gα-interacting vesicle-associated protein; also known as Girdin), enhances Akt activation downstream of multiple growth factor– and G-protein–coupled receptors to trigger cell migration and cancer invasion. Here we demonstrate that GIV is a tyrosine phosphoprotein that directly binds to and activates phosphoinositide 3-kinase (PI3K). Upon ligand stimulation of various receptors, GIV was phosphorylated at Tyr1764 and Tyr1798 by both receptor and non-receptor tyrosine kinases. These phosphorylation events e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
148
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 77 publications
(160 citation statements)
references
References 77 publications
(205 reference statements)
12
148
0
Order By: Relevance
“…expression is supported by our results presented here (Fig. S4C) and by previous observations (29) showing that Akt activation is gradually increased in cells of isogenic background from the 21T series that represent different stages of cancer progression and naturally express increasing levels of GIV. However, for a given number of GIV copies, Akt signaing is ultrasensitive to the level of GEF activity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…expression is supported by our results presented here (Fig. S4C) and by previous observations (29) showing that Akt activation is gradually increased in cells of isogenic background from the 21T series that represent different stages of cancer progression and naturally express increasing levels of GIV. However, for a given number of GIV copies, Akt signaing is ultrasensitive to the level of GEF activity.…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it is tempting to speculate that the ultrasensitive response to GIV's GEF activity is a consequence of this dual effect of activating the G protein and displacing its GDIs; however, we cannot rule out other possibilities such as the existence of regulatory feedback loops and/or synergy with other components of this pathway. For example, it is possible that the ultrasensitive Akt response arises from the cooperative action of GIV's GEF activity and the direct activation of PI3K by tyrosine phosphorylated GIV (29).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with the central role of GIV's GEF function in the enhancement of EGFR autophosphorylation (9, 30) and PI3K-Akt signaling downstream (7,29), transduction with TAT-GIV-CT-FA inhibited receptor autophosphorylation (as determined by phosphorylation at Y1068 and Y1173 on EGFR tail; ref. Fig.…”
Section: Cell-permeable Giv-ct Peptides Are Effective In Exogenous Momentioning
confidence: 57%
“…The rationale for the design of these peptides is multifactorial: (i) a complete phylogenetic analysis of GIV (17) has revealed that this stretch of GIV's C terminus could be functionally autonomous because it evolved independently of its N terminus (in fish), and both N-and C-termini fused into full length GIV only in birds; (ii) the C terminus contains the GEF and SH2-like domains (Fig. 1B), representing the cross-road between GPCR/G and RTK signaling pathways; (iii) the C terminus of GIV also contains the two critical tyrosines (Y1764 and Y1798) that serve as docking sites for p85α(PI3K) (29); (iv) the coexistence of those tyrosines, the GEF motif, and the SH2-like domain is restricted only to the most complex of eukaryotes, i.e., mammals, and is highly conserved (∼99%) (17,29); (v) biochemical and functional assays (9,25) have convincingly demonstrated that the critical C-terminal domain is necessary and sufficient for GIV to carry out its functions during signal transduction downstream of RTKs; and finally, (vi) biophysical studies (25) have revealed that fluorescent GIV-CT biosensors are effective tools for visualization and manipulation of the fundamental function of GIV in signal transduction, i.e., enabling dynamic association of Gαi with RTKs and noncanonical transactivation of G proteins in cells responding to growth factors. We expressed and purified (∼95-99% purity) the TAT-GIV-CT peptides and confirmed that they were expressed as proteins of expected size by immunoblotting ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation